Le Guide agricole. Cultures légumières - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Ce guide est dans le droit fil des précédentes publications de l'AREU, traitant notamment des arbres